Aquaculture promotion through Agricultural Technology Management Agency - a case study in Kerala - Joshua, Nisha Elizabeth; Ojha, S.N. (Indian Journal of Fisheries, 2016)
Agricultural Technology Management Agency (ATMA) is an autonomous body that has linkage with all the line departments, like Department of Fisheries (DoF), that works towards raising farmer’s income and involved in formulation of suitable strategies for empowering the farmers. In this study, ATMA impact factors among fish farmers were reviewed and discussed with the local officers. The impact factors considered were the types of culture, number of species cultured, yield disposition, marketing and expenditure in fish farming. It was observed, from a sample of 225 fish farmers, that Alappuzha, Ernakulam and Kollam districts responded more towards ‘type of culture’ and less towards ‘marketing’, whereas Kottayam and Thrissur districts responded more towards marketing. Among all the impact factors, expenditure on aquaculture was found to be significantly associated with income in all the five districts. This was followed by marketing (4 districts), yield disposition (3 districts), fish species cultured (3 districts) and type of culture (2 districts). On the contrary, it was observed that ATMA support was not similarly associated with these factors, especially for yield disposition and marketing in aquaculture. Therefore, suitable strategies are recommended to strengthen the supply chain management through ATMA.